Serum endotoxin, inflammatory mediators, and magnetic resonance spectroscopy before and after treatment in patients with minimal hepatic encephalopathy. Issue 7 (20th June 2013) - Jain, Lokesh; Sharma, Barjesh Chander; Srivastava, Siddharth; Puri, Sunil Kumar; Sharma, Praveen; Sarin, Shiv
Abstract: Background: Minimal hepatic encephalopathy (MHE) represents the mildest form of hepatic encephalopathy (HE), with abnormal neuropsychologic findings. Inflammatory response may be important in the pathogenesis of MHE. On magnetic resonance spectroscopy (MRS), improvement of metabolic ratios after liver transplantation suggests an important role of myoinositol (mI) and choline (cho) in the development of MHE. Aims: To investigate arterial ammonia, tumor necrosis factor alpha (TNF‐α), interleukin (IL)‐6, IL‐18, serum endotoxin, and MRS before and after treatment in MHE. Patients and Methods: Sixty patients of cirrhosis with MHE were randomized to two groups, Gr. MHE‐L ( n  = 30), treated with lactulose for 3 months, and Gr. MHE‐NL ( n  = 30), who did not received lactulose. Arterial ammonia, TNF‐α, IL‐6, IL‐18, serum endotoxin, and MRS were performed in all patients at baseline and at 3 months and 20 patients of cirrhosis without MHE and 20 healthy controls. Results: After 3 months, median arterial ammonia (69.4 vs 52.7 mcg/dL), TNF‐α (26.6 vs 22 pg/mL), IL‐6 (17.6 vs 12.4 pg/mL), IL‐18 (42.5 vs 29 pg/mL), and serum endotoxin (0.68 vs 0.43 EU/mL) significantly decreased in Gr. MHE‐L compared with baseline ( P  < 0.0001), while no change was seen in Gr. MHE‐NL patients. On MRS, compared with patients of cirrhosis without MHE, mI and cho were significantly lower ( P  < 0.001) and glutamine (Glx) was significantly higher in both MHE groups ( P  < 0.001). After 3 months, mI and cho increased and Glx decreased significantly in Gr. MHE‐L ( P  < 0.001), without changes in Gr. MHE‐NL patients. Psychometric hepatic encephalopathic score (PHES) correlated well with arterial ammonia, TNF‐α, IL‐6, IL‐18, serum endotoxin, and metabolic parameters on MRS. Conclusions: Arterial ammonia, inflammatory mediators (TNF‐α, IL‐6, IL‐18), and serum endotoxin reduce and MRS abnormalities improve after treatment with lactulose in patients with MHE.